Effect of sheep manure on yield, nutritional value and antioxidant capacity of green tomato (Physalis ixocarpa) - Aguiñaga-Bravo, Arturo; Medina-Dzul, Kati; Garruña-Hernández, René; Latournerie-Moreno, Luis; Ruíz-Sánchez, Esaú (Acta Universitaria, 2020)
The effect of the addition of bocashi or sheep manure, mixed with 50% of synthetic fertilizers was evaluated in green tomato. Physiological variables, biomass production, fruit yield, and mineral foliar content, nutritive value and antioxidant capacity of the fruit were studied. The biomass and the yield of the fruit do not present differences between the treatments, except for the root biomass. The accumulation of N was greater in the foliage of plants with sheep manure + chemical fertilization 50% (SM-ChF 50%), the transpiration rate was higher, and the stomatal conductance was lower. The accumulation of P and K did not vary between treatments. The contents of fat, Ca, K, Fe, and total phenols were higher in fruits with SM-ChF 50%. The addition of organic fertilizer with 50% chemical fertilization equals yields and improves the quality of the green tomato (P. ixocarpa).